Empowerment of female farmers through catfish culinary in industrial areas - Jubaedah, Yoyoh; Maosul, Asep; Rinekasari, Nenden Rani; Yusuf, Rakhmat; Rohaeni, Neni; Hernawati, Heni (Jurnal Abmas, 2026)
Catfish farmers face marketing challenges, resulting in delayed harvests and significant price declines. This program aims to improve the economic capacity of women's farmer groups through catfish-based culinary training in Sukamanah Village, Rancaekek District, an area impacted by industrial waste. The method used was a participatory, learning-by-doing model and a Training-of-Trainers (ToT) approach. The program was implemented over six months, encompassing needs analysis, training, mentoring, and evaluation. Results showed significant improvements in participants' knowledge, food processing skills, and product innovation capabilities. The resulting products, such as siomay (siomay), tofu meatballs, and fried catfish dumplings, have a high level of acceptance and have the potential to become household-based micro-enterprises. This program also contributes to women's empowerment by increasing productivity and family income. Furthermore, the digital-based mentoring approach and the role of PKK (Family Welfare Movement) cadres as local agents have proven to support the program's sustainability. Thus, culinary training based on local potential can be an effective strategy for improving family welfare in areas affected by industrial pollution.
Keywords: catfish; empowerment of female farmers; family welfare; food product diversification